Access to Finance for African SMEs: Do Women Entrepreneurs face Discrimination. - Taqi, Muhammad; Shah, Salyha Zulfiqar Ali; Ali, Muhammad Sibt e; Ali, Muhammad; Yousuf, Muhammad (The journal of contemporary issues in business and government, 2021)
This study examines the gender disparity in Africa‟s small and medium business (SME) credit market. It shows how capital market imperfections can lead to second best solutions, so this research is significant for emerging economies. The gender gap between men and women is still there in Africa, and unless particular efforts are made to address the underlying issues today, it will continue to increase. The fact that black women make up the majority of the self-employed population isn’t reflected in present industry targets for company activity, which is a problem. Women-owned businesses in Africa face unique problems, and this study evaluates whether financial service providers in the country are adequately aware of these issues.